Design, Synthesis, and Biological Activity of Novel Chalcone Derivatives Containing an 1,2,4-Oxadiazole Moiety - Luo, Ling; Liu, Dan; Lan, Shichao; Gan, Xiuhai (Frontiers in Chemistry, 2022)
To discover a lead compound for agricultural use, 34 novel chalcone derivatives containing an 1,2,4-oxadiazole moiety were designed and synthesized. Their nematocidal activities against Bursaphelenchus xylophilus, Aphelenchoides besseyi, and Ditylenchus dipsaci and their antiviral activities against tobacco mosaic virus (TMV), pepper mild mottle virus (PMMoV), and tomato spotted wilt virus (TSWV) were evaluated. Biological assay results indicate that compounds A13 and A14 showed good nematocidal activities against B. xylophilus, A. besseyi, and D. dipsaci, with LC50 values of 35.5, 44.7, and 30.2 μg/ml and 31.8, 47.4, and 36.5 μg/ml, respectively, which are better than tioxazafen, fosthiazate, and abamectin. Furthermore, compound A16 demonstrated excellent protective activity against TMV, PMMoV, and TSWV, with EC50 values of 210.4, 156.2, and 178.2 μg/ml, respectively, which are superior to ningnanmycin (242.6, 218.4, and 180.5 μg/ml).